Numerical simulations of two-dimensional neural fields with applications to working memory - Lima, Pedro M. (2018)
In this paper we describe a neural field model which explains how a population of cortical neurons may encode in its firing pattern simultaneously the nature and time of sequential stimulus events. From the mathematical point of view, this is obtained my means of a two-dimensional field, where one dimension represents the nature of the event (for example the color of a light signal) and the other represents the elapsed time. Some numerical experiments are reported which were carried out using a computational algorithm for two-dimensional neural field equations. These numerical experiments are described and their results are discussed.